Diversification and performance: evidence from East Asian firms - Chakrabarti, Abhirup; Singh, Kulwant; Mahmood, Ishtiaq (Strategic Management Journal, 2007)
Abstract We examine the impact of diversification on performance for firms operating in different institutional environments during a relatively stable period and during a major economy‐wide shock. We locate our study in six Asian countries at different levels of institutional development. Results indicate that diversification negatively impacts performance in more developed institutional environments while improving performance only in the least developed environments. Even in the least developed institutional environments, diversification offers limited benefits when an economy‐wide shock strikes. Though successful diversifiers are sometimes affiliated with business groups, diversification is associated with poorer performance for both affiliated firms and independent firms. In sum, we find that the outcomes of diversification are influenced by institutional environments, economic stability and affiliation with business groups. Copyright © 2007 John Wiley & Sons, Ltd.